Torcal de Antequera – stony town from Andalucia - Janusz, Małgorzata; Lorenc, Marek W. (Geotourism/Geoturystyka, 2025)
The Torcal de Antequera is one of the best-preserved karst landscapes in Europe developed in Jurassic, oolithic, brecciated and detrital limestones. The rock formation is wellbedded and cut by a dense, regular fracture system. A relatively small area (20 km2) comprises four distinct geomorphological zones. At the surface visitors can recognize a variety of landforms produced by water and wind erosion whereas underground there exists a labirynth of karst forms: deep shafts, meandering galleries and huge caves. Since 1978 the Torcal de Antequera has been protected as a Natural Park and since 1989 it has become a Nature Site. The park combines a collection of remarkable geological valours and an exceptional biodiversity.